Perlindungan Hukum terhadap Konsumen atas Ketidaksesuaian Barang dalam Transaksi E-Commerce di Indonesia - Adelia Zulfeni; Zakkia Laeha Zalma; Holijah . (CV. ITTC INDONESIA, 2026)
The development of information technology has brought significant changes in various aspects of life, particularly in the field of trade through electronic systems or e-commerce. Online buying and selling transactions provide convenience for the public as they can be carried out practically without limitations of space and time. However, these conveniences are also accompanied by various problems that may cause losses to consumers, such as discrepancies between goods and their descriptions, poor product quality, delays in delivery, or even failure to deliver goods after payment has been made. This study aims to analyze legal protection for consumers in online buying and selling transactions as well as the responsibility of business actors for losses experienced by consumers. The method used in this study is normative legal research with a statutory and conceptual approach. The results of the study indicate that consumer protection has been regulated in Law Number 8 of 1999 and Law Number 11 of 2008, but in practice, it still faces various obstacles. Therefore, increased supervision and public legal awareness are needed to ensure better consumer protection.